Analisis Pengaruh Ekonomi Indonesia Terhadap Rupiah - Andhika. S, I Komang; Rachman. Z, Abdillah; Dhiya. A, Shopiyah; Simanjuntak, Adelia (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyse the effect of exchange rates and inflation on Indonesia's economic growth during the period 2014–2023. Economic growth is measured by GDP percentage, exchange rates using the USD/IDR middle rate, and inflation using the general inflation percentage. This study uses a quantitative approach with multiple linear regression analysis. The data used is annual secondary data obtained from the Central Statistics Agency (BPS) and Bank Indonesia (BI). The results show that the exchange rate has a negative effect on economic growth. The strengthening of the dollar against the rupiah tends to suppress exports and production activities, thereby slowing economic growth. Meanwhile, inflation has a negative effect on economic growth because high inflation can weaken people's purchasing power and increase production costs. Both variables have been proven to have a significant effect on Indonesia's economic growth. These findings can be taken into consideration by the government and economic actors in formulating policies that focus on exchange rate stability and inflation control to support sustainable economic growth